2023
DOI: 10.1155/2023/6399699
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Antibiotic Susceptibility and Antimicrobial Potential of Bacteria from Human Breast Milk of Pakistani Women: An Exploratory Study

Abstract: Background. Human life quality and expectancy have increased dramatically over the past 5 decades because of improvements in nutrition and antibiotic’s usage fighting against infectious diseases. Yet, it was soon revealed that the microbes adapted to develop resistance to any of the drugs that were used. Recently, there is great concern that commensal bacteria from food and the gastrointestinal tract of humans and animals could act as a reservoir for antibiotic resistance genes. Methodology. This study was int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…It causes the inactivation of the RNA polymerase active site to bind and confer RIF resistance. The hotspot rpoB gene mutation confirmation using multiplex allele-specific PCR (MAS-PCR) proves that the mutation frequency was higher at codons 531, 526, and 516. , …”
Section: Mechanism Of Antimicrobial Resistance In Mycobacterium Tuber...mentioning
confidence: 98%
See 1 more Smart Citation
“…It causes the inactivation of the RNA polymerase active site to bind and confer RIF resistance. The hotspot rpoB gene mutation confirmation using multiplex allele-specific PCR (MAS-PCR) proves that the mutation frequency was higher at codons 531, 526, and 516. , …”
Section: Mechanism Of Antimicrobial Resistance In Mycobacterium Tuber...mentioning
confidence: 98%
“…The hotspot rpoB gene mutation confirmation using multiplex allele-specific PCR (MAS-PCR) proves that the mutation frequency was higher at codons 531, 526, and 516. 52,53 4.3. Metabolic Bypass.…”
Section: Hotspot Mutation In Genes For Drug Resistancementioning
confidence: 99%
“…Several studies have highlighted that the gut microbiota of breastfed newborns is dominated by bifidobacterial strains. Earlier studies often described the 'bifidogenic' impact of human milk, referring to the enrichment of beneficial microbiota in an infant's gut via HMOs [2,23,32,47]. HMOs are resistant to newborns' digestion as the newborn lacks glycolytic enzymes.…”
Section: Modulation Of Gut Microbial Compositionmentioning
confidence: 99%
“…However, there is still much to learn about how HMOs are specifically metabolized by beneficial microbiota in the newborn's gastrointestinal environment. Generally, HMOs are transformed by the microbiota into short-chain fatty acids (SCFAs) which contribute to the establishment of stable and healthy gut microbiomes [23,47,52]. The study by Schwab et al [53] showed that B. breve, and B. longum subsp.…”
Section: Modulation Of Gut Microbial Compositionmentioning
confidence: 99%
See 1 more Smart Citation